Lecture 37: Terminology: Maclaurin Polynomials of a Function F(X) Are the Taylor Polynomials at a = 0

Lecture 37: Terminology: Maclaurin Polynomials of a Function F(X) Are the Taylor Polynomials at a = 0

Lecture 37: Terminology: Maclaurin polynomials of a function f(x) are the Taylor polynomials at a = 0. See Table 5, p. 278, for famous Maclaurin polynomials. Recall simple properties of big O: 1. If f(x) = O(u(x)) as x ! a, then Cf(x) = O((u(x)) for any C. 2. If f(x) = O(u(x)) and g(x) = O(u(x)) as x ! a, then f(x) ± g(x) = O(u(x)) as x ! a (use triangle inequality). 3. If f(x) = O((x − a)ku(x)) as x ! a, then f(x) = O(u(x)) (x−a)k as x ! a. (note that technically f(x) need not be defined at a; so f(x) = (x−a)k (x−a)k O(u(x)) should be taken to mean that there is a constant K > 0 s.t. for all x =6 a in an open interval containing a, j f(x) j < Kju(x)j. (x−a)k 4. If f(x) = O(u(x)) as x ! a and u(x) = O(w(x)) as x ! a, then f(x) = O(w(x)). Recall Theorem 13: If f(x) = Q(x) + O((x − a)n+1(x) as x ! a, for some polynomial Q(x) of degree at most n, then Q(x) = Pn(x). Application of Theorem 13: Find Taylor polynomials of a function from Taylor polynomials of other functions, without computing any new derivatives. Example: Compute Taylor polynomials for f(x) = e2x at a = 1: Use Maclaurin polynomials for ex: e2x = e2e2(x−1) = 1 22(x − 1)2 2n(x − 1)n = e2(1+2(x−1)+ +:::+ +O(2n+1(x−1)n+1) 2 n! 22(x − 1)2 2n(x − 1)n = e2(1 + 2(x − 1) + + ::: + ) + O((x − 1)n+1) 2 n! (by property 1, multiplication by a constant preserves big O). So, by Theorem 13, n-th Taylor polynomial for e2x at a = 1 is: 22(x − 1)2 2n(x − 1)n e2(1 + 2(x − 1) + + ::: + ): 2 n! Of course, this is easy enough to verify directly: f (n)(x) = 2ne2x and so f (n)(1) = 2ne2 Example: Compute Maclaurin polynomials for ex + e−x cosh(x) = 2 x Let Pn(x) be the n-th Taylor polynomial for e ; a = 0. x 2n+2 e = P2n+1(x) + O(x ) = 1 + x + x2=2 + x3=3! + ::: + x2n+1=(2n + 1)! + O(x2n+2) −x 2n+2 e = P2n+1(−x) + O(x ) = 1 − x + x2=2 − x3=3! + ::: − x2n+1=(2n + 1)! + O(x2n+2) So by property 2 (big O is preserved under sums and differences) P (x) + P (−x) cosh(x) = 2n+1 2n+1 + O(x2n+2) 2 = 1 + x2=2 + x4=4! + ::: + x2n=(2n)! + O(x2n+2) By Theorem 13, 1 + x2=2 + x4=4! + ::: + x2n=(2n)! 2 is the (2n + 1)-th Taylor polynomial for cosh(x) at a = 0. Since the degree of Q(x) is 2n, it is also the 2n-th Taylor poly- nomial because, by property 4 above, if g(x) = O(x2n+2), then g(x) = O(x2n+1). Hyperbolic functions: Defn of cosh(x); sinh(x). ex + e−x ex − e−x cosh(x) := ; sinh(x) = 2 2 Derivatives: ex − e−x ex + e−x cosh0(x) = = sinh(x); sinh0(x) = = cosh(x) 2 2 So, for f(x) = cosh(x), f (2n)(x) = cosh(x); f (2n)(0) = cosh(0) = 1 f (2n+1)(x) = sinh(x); f (2n+1)(0) = sinh(0) = 0 (this directly verifies the Maclaurin polynomials for cosh(x) above). Sketch the graph of cosh(x): add ex and e−x and divide by 2 (equivalently, cosh(x) is the average of ex and e−x). Appears to have an abs. min at x = 0, is always concave up and limx→±∞ cosh(x) = 1. { Indeed, critical point for f(x) = cosh(x): f 0(x) = sinh(x) = 0, which mean ex = e−x and so e2x = 1 and so x = 0. And f 00(x) = cosh(x) > 0. Shape of a hanging cable and other applications. 3 Sketch the graph of sinh(x): subtract e−x from ex and divide by 2. Appears to have no relative extrema, but an inflection point at 0 and limx!1 sinh(x) = 1, limx→−∞ sinh(x) = −∞, { Indeed, no critical point for g(x) = sinh(x) because g0(x) = cosh(x) > 0 And g00(x) = sinh(x), which is + for x > 0 and - for x < 0. Fact: cosh2(x) − sinh2(x) = 1. Proof: cosh2(x) − sinh2(x) = (1=4)((e2x + 2 + e−2x) − (e2x − 2 + e−2x) = 1: So, for all t, (cosh(t); sinh(t)) lies on the hyperbola x2 − y2 = 1, and this explains why they are called \hyperbolic" functions. In fact, this gives a 1:1 parametrization of the right half of the hyperbola: { in the right half because cosh(t) is always > 0. { 1:1 because |{ the vertical coordinate is increasing with t: sinh0(t) = cosh(t) > 0 { covers the entire right half because limx!1 sinh(x) = 1, limx→−∞ sinh(x) = −∞, Hyperbolic functions are given \trigonometric" names because they mimic cos and sin: (cos(t); sin(t)) parameterizes the unit circle (but not 1-1). e.g., cosh(x) is even and sinh(x) is odd. 4 Other hyperbolic functions, e.g.: sinh(x) tanh(x) := cosh(x) And there are inverse hyperbolic functions. 5 Lecture 38: Recall: Defn: An anti-derivative of a function f is a function F s.t. F 0(x) = f(x). Defn: The general anti-derivative or indefinite integral of a func- tion f is written Z f(x)dx = F (x) + C where F is any particular anti-derivative and C is an arbitrary con- stant. Makes sense because Fact: Functions F and G defined on an interval I are anti-derivatives of the same function if and only if F − G is a constant. Proof: If F − G = C, then F 0 − G0 = 0 and so F 0 = G0. Conversely, if F 0 = G0 on I, then (F − G)0 = 0 on I, and we showed long ago, by the MVT, that F − G is a constant. Note: this assumes that the common domain is an interval. Consider (0; 1) [ (2; 3) F = 0;G = 0 on (0; 1);G = 1 on (2; 3) Recall the Examples on p. 150 and R (1=x)dx = ln(jxj) + C: Recall: Earlier we discussed differential equations a bit: A first order differential equation is an equation of the form: dy = f(x; y) dx A solution to the differential equation is a function y = y(x) which satisfies the equation. 6 @f Under mild assumptions on f (continuity of f and @y ), there al- ways exists a solution and the solution is uniquely determined once one specifies and initial condition y(x0) = y0. Special case: f(x; y) = f(x). | A solution is the same thing as an anti-derivative. | An initial condition uniquely determines the constant of inte- gration. Example: Solve y0 = 6x2 − 1; y(2) = 10: y = y(x) = 2x3 − x + C 10 = 16 − 2 + C C = −4: Solution: y = y(x) = 2x3 − x − 4. Recall also another special case: . y0 = ky. We showed that the solution is y = y(x) = Cekx and is uniquely determined by an initial condition y(x0) = y0: kx0 y0 = Ce So, y C = 0 ekx0 A second order differential equation is of the form: y00 = f(t; y; y0) @f @f Again, under mild conditions on f (continuity of f and @y ) and @y0 , there always exists a solution and the solution is uniquely determined 0 0 once one specifies and two initial conditions y(x0) = y0; y (x0) = y0. 7 Special case: f(x; y; y0) = f(x). | A solution is the same thing as an second anti-derivative, which will have two arbitrary constants. | Initial conditions uniquely determine the two constants of inte- gration. Example: Solve y00 = sin(x); y(π) = 2; y0(π) = −1: y0 = − cos(x) + C −1 = − cos(π) + C C = −2 y0 = − cos(x) − 2 y = − sin(x) − 2x + D 2 = − sin(π) − 2π + D D = 2 + 2π: y = − sin(x) − 2x + 2 + 2π: 8 Lecture 39: Review Lecture 40: Midterm 2 9.

View Full Text

Details

  • File Type
    pdf
  • Upload Time
    -
  • Content Languages
    English
  • Upload User
    Anonymous/Not logged-in
  • File Pages
    9 Page
  • File Size
    -

Download

Channel Download Status
Express Download Enable

Copyright

We respect the copyrights and intellectual property rights of all users. All uploaded documents are either original works of the uploader or authorized works of the rightful owners.

  • Not to be reproduced or distributed without explicit permission.
  • Not used for commercial purposes outside of approved use cases.
  • Not used to infringe on the rights of the original creators.
  • If you believe any content infringes your copyright, please contact us immediately.

Support

For help with questions, suggestions, or problems, please contact us